Os Territórios de desmatamento na Amazônia. Uma análise geográfica no Estado do Pará. - René Poccard-Chapuis; Marcelo Cordeiro Thalês; Jaqueline De Carvalho Peçanha; Marie-Gabrielle Piketty (Confins)
Deforestation rates in the Amazon achieve a floor rates in 2012, and are slow growing since 2013, questioning the scientific community about the causes of this persistence. The article presents an original methodology, analyzing the official annual data of deforestation, within a territorial focus and based on the systemic concepts of frontier margins dynamics. The authors elaborate a municipal typology, where each type is a step for territorial construction, and where deforestation assumes specific roles. The authors demonstrate the existence of deforestation territories, and others where development is not more based on new deforestations. Based on this analysis, the authors formulate suggestions for public policies and strategies to tackle persistent deforestations and to promote sustainable development in every territorial situation.